STEAM-Project Based Learning (PjBL): Efforts to Train Critical Thinking Skills for Prospective Science Teacher - Dyah Astriani; Martini; Laily Rosdiana; An Nuril Maulida Fauziah; Aris Rudi Purnomo (Jurnal Penelitian Pendidikan IPA, 2023)
The implementation of STEAM-PjBL integration trains students to work together to build their own knowledge, construct ideas, critical thinking in analyzing problems, then try to solve them through a project. The purpose of this study was to determine the effectiveness of STEAM-PjBL integration to train the critical thinking skills of prospective science teachers through entrepreneurship courses. This research is a descriptive study with a one short case study design. The research subjects were students of Science Education Class of 2021. The instruments used were tests of critical thinking skills and questionnaires on student responses to learning. Test result were analyzed using N-gain and paired t test, the response questionnaire was analyzed descriptively. The results showed an increase in students' critical thinking skills test scores, and positive responses with an average of >83.6%. Based on this, it can be concluded that STEAM-PjBL integration is effective in improving students' critical thinking skills.